Investigation of different process routes for joining thermoplastic composite/steel joints via the embedding of cold formed metallic pin structures - Popp, Julian; Drummer, Dietmar (Journal of Advanced Joining Processes, 2024)
This study focuses on the integration of continuous fiber-reinforced thermoplastics (CFRT) with metal components through the use of cold-formed pin structures. Comparing six different joining methods with varying heat generation approaches, we investigated their impact on the mechanical properties and joint integrity. Ultrasonic vibration emerged as a highly promising method, offering both rapid joining operations and favorable mechanical characteristics with average failure loads in lap shear tests of up to 249 N. In comparison, vibration welding showed drawbacks, resulting in CFRT damage, potential pin failure, and diminished mechanical performance with maximum average lap shear loads of 216 N. Additionally, traces of zinc residue were identified on the CFRT surface, raising concerns about the corrosion resistance of the metal component. In summary, vibration welding appears unsuitable for pin joining applications. Infrared heating, while showcasing good mechanical performance with lap shear loads of up to 257 N, proved to be a more time-consuming process compared to ultrasonic joining. It also resulted in inferior mechanical strength under shear load in the direction of the fiber orientation (238 N). To assess the mechanical potential of pin joints relatively to established joining methods, we created and tested adhesively joined reference samples. Pin joints demonstrated a significant advantage under shear load, showing approximately double the shear strength (17.8 MPa) compared to adhesively joined samples (8.9 MPa). However, under normal load, pin joints exhibited lower strength, highlighting the need for further optimization to enhance their practical applicability.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Continous fiber reinforced thermoplastic; Glass fiber; Hybrid joining; Pin; Thermoplastic composites